An avian seed dispersal paradox: New Zealand's extinct megafaunal birds did not disperse large seeds. Issue 1877 (25th April 2018) - Carpenter, Joanna K.; Wood, Jamie R.; Wilmshurst, Janet M.; Kelly, Dave
Abstract : Often the mutualistic roles of extinct species are inferred based on plausible assumptions, but sometimes palaeoecological evidence can overturn such inferences. We present an example from New Zealand, where it has been widely assumed that some of the largest-seeded plants were dispersed by the giant extinct herbivorous moa (Dinornithiformes). The presence of large seeds in preserved moa gizzard contents supported this hypothesis, and five slow-germinating plant species ( Elaeocarpus dentatus, E. hookerianus, Prumnopitys ferruginea, P. taxifolia, Vitex lucens ) with thick seedcoats prompted speculation about whether these plants were adapted for moa dispersal. However, we demonstrate that all these assumptions are incorrect. While large seeds were present in 48% of moa gizzards analysed, analysis of 152 moa coprolites (subfossil faeces) revealed a very fine-grained consistency unparalleled in extant herbivores, with no intact seeds larger than 3.3 mm diameter. Secondly, prolonged experimental mechanical scarification of E. dentatus and P. ferruginea seeds did not reduce time to germination, providing no experimental support for the hypothesis that present-day slow germination results from the loss of scarification in moa guts. Paradoxically, although moa were New Zealand's largest native herbivores, the only seeds to survive moa gut passage intact were those of small-seeded herbs and shrubs.